Pengaruh Earning Per Share, Debt To Equity Ratio, Current Ratio, dan Investment Opportunity Set Terhadap Kebijakan Dividen Perusahaan Sub Sektor Produksi Batu Bara - Alifia Putri Amelia Rohmawaty; Rika Wijayanti; Padma Adriana Sari (Politeknik Negeri Malang, 2024)
The purpose of this study was to determine the effect of Earnings Per Share (EPS), Debt to Equity Ratio (DER), Current Ratio (CR), and Investment Opportunity Set (IOS) on dividend policy in Coal Production Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2018– 2021. This study is quantitative descriptive and documentation techniques are used to obtain data. There are 19 companies in the coal production sub-sector, all of which are listed on the Indonesia Stock Exchange. The sample determination was carried out by purposive sampling and 8 samples were obtained. The secondary data used were financial statements from 2018 to 2021, then analyzed using a multiple linear regression model in SPSS version 26. The results showed that DER and IOS partially had a significant effect on the Dividend Payout Ratio (DPR), while EPS and CR did not affect the DPR. DPR is simultaneously influenced by EPS, DER, CR, and IOS. For this purpose, companies must pay attention to the ability to buy debt and future discovery opportunities to consider dividend payments to shareholders.